2019
DOI: 10.1089/neu.2018.5687
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Developmental Outcomes after Traumatic Brain Injury in Young Children: Are Infants More Vulnerable Than Toddlers?

Abstract: Children under 4 years of age have the highest incidence of traumatic brain injury (TBI) among the non-elderly and may be at high risk of poor developmental outcomes. We prospectively enrolled a cohort of children injured before 31 months old with TBI or orthopedic injury (OI), from 2013 to 2015 at two pediatric level 1 trauma centers to study very young children's developmental outcomes after injury. We used Ages & Stages-3 and Ages & Stages: Social-Emotional screening tools to measure children's development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 36 publications
1
27
1
1
Order By: Relevance
“…Very young children may be particularly vulnerable to the effects of TBI as the brain is under continuous development throughout childhood (2). Pediatric survivors of TBI are at increased risk for worse behavioral, social, and academic outcomes compared to their peers (3)(4)(5)(6). Moreover, pediatric survivors of TBI show high incidence of health issues including pain, cardiovascular, and metabolic disorders (2).…”
Section: Introductionmentioning
confidence: 99%
“…Very young children may be particularly vulnerable to the effects of TBI as the brain is under continuous development throughout childhood (2). Pediatric survivors of TBI are at increased risk for worse behavioral, social, and academic outcomes compared to their peers (3)(4)(5)(6). Moreover, pediatric survivors of TBI show high incidence of health issues including pain, cardiovascular, and metabolic disorders (2).…”
Section: Introductionmentioning
confidence: 99%
“…Injury severity was considered in 11 studies. 20,30,33,34,[39][40][41]45,46,48,52,55 A positive correlation between severity of injury and presence of deficits was consistently reported in all outcomes. As mentioned in relation with specific outcome areas, children who experienced moderate or severe TBIs tended to demonstrate a greater range of or more significant deficits when compared with children with mild TBI.…”
Section: Outcomes Of Early Childhood Tbi and Areas Of Needmentioning
confidence: 67%
“…14 Eighteen studies reported on psychosocial and behavioral outcomes. 14,16,30,34,37,39,43,[45][46][47][48][49][50][51][52][53][54][55] Generally, social functioning was negatively impacted following early childhood TBI, independent of severity. Acutely, children who experienced a TBI before 6 years of age demonstrated decreased play engagement, including gaze initiation and joint attention.…”
Section: Outcomes Of Early Childhood Tbi and Areas Of Needmentioning
confidence: 97%
See 2 more Smart Citations